2021
DOI: 10.1002/aic.17243
|View full text |Cite
|
Sign up to set email alerts
|

Advanced absorber heat integration via heat exchange packings

Abstract: A rate‐based model of an absorption column was developed and used to analyze several intercooling strategies utilizing “heat exchange packings.” These packings are capable of removing heat from the column and transferring it to a cooling fluid within the packing. For absorption of CO2 into aqueous monoethanolamine under industrial conditions, intercooling via heat exchange packings placed along 10–20% of the column could reduce the column height by ∼15%. The height of these columns was close to the minimum the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Many works have demonstrated that structured packings could provide a large effective interfacial surface to realize efficient CO 2 removal from combustion flue gas 6–8 . Although the dimension of the absorber column is significantly reduced as a result of the existing structured packings, it is still one of the largest and priciest device in the purchased equipment for absorption‐based CO 2 capture plant 9 …”
Section: Introductionmentioning
confidence: 99%
“…Many works have demonstrated that structured packings could provide a large effective interfacial surface to realize efficient CO 2 removal from combustion flue gas 6–8 . Although the dimension of the absorber column is significantly reduced as a result of the existing structured packings, it is still one of the largest and priciest device in the purchased equipment for absorption‐based CO 2 capture plant 9 …”
Section: Introductionmentioning
confidence: 99%